Involvement of small and medium sized enterprises in the private realisation of public buildings - Bastian Heinecke (Technische Universität Bergakademie Freiberg, Fakultät für Wirtschaftswissenschaften, 2002)
This paper explores the procurement of public buildings in local authorities in the UK under the Private Finance Initiative (PFI) and its consequences for small and medium sized enterprises. Following an outline of the development of PFI in the UK, the paper explains the peculiarities of local authorities' involvement. Opportunities and problems of smaller constructors in such PFI projects are then analysed. Three case studies of smaller PFI schemes are reviewed including procurement process, contract agreement, project funding, risk allocation and innovations. Because of complicated approval frameworks and contract structures more and more projects are bundled in order to obtain a better value for money. Smaller constructors, therefore, can only act as subcontractors until simpler procedures and contracts are introduced by government bodies and organisations responsible. – – Die vorliegende Arbeit setzt sich mit der Beschaffung öffentlicher Gebäude in Kommunen in UK im Rahmen der Private Finance Initiative (PFI) und den daraus resultierenden Folgen für klein und mittelständische Betriebe auseinander. Nach einem kurzen Überblick über die PFI in UK werden die Besonderheiten für Kommunen im Rahmen der PFI deutlich gemacht. Die Möglichkeiten und Probleme der kleineren Baubetriebe sind dabei genauer untersucht worden. Drei Fallstudien kleinerer PFI Projekte wurden anhand der Kriterien Beschaffungsprozess, Vertragsgestaltung, Projektfinanzierung, Risikoverteilung und Neuerungen ausgearbeitet und analysiert. Aufgrund komplexer Bewilligungsverfahren und Vertragsgebilde werden immer mehr Projekte gebündelt um einen besseren Mehrwert zu erzielen. Kleinere Baubetriebe agieren dabei nur als Subunternehmer, solange keine Vereinfachungen durch die zuständigen Behörden und Organisationen realisiert werden.
Keywords: H54; H57; L33; L74; 330; Private Finance Initiative; Infrastructure; SME; Local Government; Privatwirtschaftliche Realisierung; Infrastruktur; KMU; Kommunalverwaltung; Öffentlicher Bau; Kommunalverwaltung; Private Infrastrukturinvestition; Klein- und Mittelunternehmen; Bauwirtschaft; Projektmanagement; Großbritannien